Adaptation of Religious Moral Values in Elementary School Education in the West Java Region, Indonesia - Sarbini (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2022)
This article seeks to examine how the implementation of moral education is presented in elementary schools (SD, SMP, and SMA) in the midst of a society that has changed from an agricultural society to an industrial society. This study aims to understand how the cognitive, affective, and psychomotor aspects of students in the implementation of religious moral values ​​are presented in schools. This study uses a qualitative method with a descriptive approach. The data collection technique taken was observation, interviews with students from primary schools (elementary, junior high and senior high schools) in the Sumberjaya District, Majalengka Regency. This study found that the religious moral values ​​presented in schools were still transfer of knowledge and religion in the aspect of cognition, only a small portion were in the affective and psychomotor aspects. Second, the socio-economic conditions of the family are part of the background for moral value education which is not optimally absorbed into the affective and psychomotor aspects. Third, the condition of the social environment has a big contribution in shaping student orientation, where religious moral values ​​do not become a control rope for students in carrying out social interactions in society. This study concludes that the implementation of religious moral values ​​in education in schools has a clash with family awareness in supporting education, learning models that are still limited to the transfer of knowledge, and the social environment of society.